2018
DOI: 10.1159/000490867
|View full text |Cite
|
Sign up to set email alerts
|

Gαi Proteins are Indispensable for Hearing

Abstract: Background/Aims: From invertebrates to mammals, Gαi proteins act together with their common binding partner Gpsm2 to govern cell polarization and planar organization in virtually any polarized cell. Recently, we demonstrated that Gαi3-deficiency in pre-hearing murine cochleae pointed to a role of Gαi3 for asymmetric migration of the kinocilium as well as the orientation and shape of the stereociliary (“hair”) bundle, a requirement for the progression of mature hearing. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 86 publications
3
51
1
Order By: Relevance
“…Downregulating Gαi activity in HCs with PTXa, inactivating both Gαi2 + Gαi3 or inactivating LGN resulted in profound deafness in young adults already (22)(23)(24)(25)(26). To explore the possibility that the disruption of the modiolar-pillar gradient of ribbon size is consecutive to the loss of sound-evoked synaptic activity, we turned to Myo15 sh2 mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulating Gαi activity in HCs with PTXa, inactivating both Gαi2 + Gαi3 or inactivating LGN resulted in profound deafness in young adults already (22)(23)(24)(25)(26). To explore the possibility that the disruption of the modiolar-pillar gradient of ribbon size is consecutive to the loss of sound-evoked synaptic activity, we turned to Myo15 sh2 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is well established that PTXa specifically ADPribosylates and impairs Gαi function(35), PTXa might affect IHC development in more ways than strictly disrupting planar polarity mechanisms. While the enlarged synaptic Ca 2+ influx observed upon PTXa argues against decreased IHC fitness or impaired IHC activity, simultaneous disruption of Gαi2 and Gαi3 was reported to impair IHC maturation(26). This conclusion was based on the absence of large-conductance Ca 2+ -activated K + (BK) channels at the IHC neck and the persistence of small-conductance Ca 2+ -activated K + (SK2) channels present before hearing onset and juxtaposed to efferent boutons.…”
mentioning
confidence: 99%
“…Several planar polarized iPCP effector modules including Rac1 and Cdc42 GTPases, cell polarity proteins, and microtubule motors act in concert to couple hair bundle orientation with kinocilium positioning (Ezan et al, 2013;Grimsley-Myers et al, 2009;Kirjavainen et al, 2015;Landin Malt et al, 2019;Siletti et al, 2017;Sipe et al, 2013;Sipe and Lu, 2011;Tarchini et al, 2013). Of particular interest, Gαi proteins and their regulators LGN/G protein signaling modulator 2 (Gpsm2) and Daple are essential for iPCP in the OC (Beer-Hammer et al, 2018;Ezan et al, 2013;Siletti et al, 2017;Tarchini et al, 2013). Here, we investigate the unsolved questions regarding the function of heterotrimeric G protein signaling and its regulation by Wnts during PCP establishment in the OC.…”
Section: Introductionmentioning
confidence: 99%
“…We and others showed that inhibitory Guanine nucleotide-binding proteins (G proteins) of the alpha family (GNAI1-3, collectively GNAI) bind the scaffold protein G Protein Signaling Modulator 2 (GPSM2) to form a complex essential for the polarized morphogenesis of the apical cytoskeleton in HCs [511]. Post-mitotic HCs are initially covered uniformly with microvilli, but planar polarized enrichment of GNAI-GPSM2 and Inscuteable (INSC) at the apical membrane defines a lateral/abneural region without protrusions, the bare zone [8].…”
Section: Introductionmentioning
confidence: 99%
“…At stereocilia tips, GNAI-GPSM2 promotes enrichment of MYO15A and other partners, conferring the first stereocilia row with its unique tallest identity [10]. Loss of GNAI or GPSM2 in mouse leads to stereocilia stunting, and the resulting immature hair bundle morphology in adults coincides with profound deafness [5, 7, 9]. In humans, mutations in GPSM2 are responsible for the Chudley-McCullough syndrome where hearing loss is the principal affliction [12, 13].…”
Section: Introductionmentioning
confidence: 99%